La Importancia Del Trabajo Comunitario Como Sanción Sustitutiva A La Privación De Libertad, En Delitos De Ínfima Cuantía - Briceño Martínez, Carlos (2016)
The present work of Thesis of Master in titled Penal Sciences; "The importance of the community work as substitute sanction to the privation of freedom, in crimes of tiny quantity", it is of great relevance and social transcendencies, because we should have present that the new tendency of the modern penal right points to application of substitute measures to the privation of freedom, previous to avoid the prison accumulation and the vulneración from the right to the individual freedom of people that for it makes trifle crimes or of little economic value they are interned in the centers of Social Rehabilitation of the Ecuador. Existing the community work as alternative sanction that he/she would help to the offender's rehabilitation. When investigating this topic, we are collapsed the penitentiary system of our country, being significant the state economic expense for the maintenance of the prisoners; where in fact social rehabilitation doesn't exist. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypotheses, allowing to support the proposed changes. The content of the thesis is the author's intellectual effort in the scientific and methodological environment that approaches theoretical and empirically, the limitation to the fundamental right of the individual rehabilitation, and in view of the ability that it grants the Code of Penal, so that you proceeds to the sanctions of a person's prison, as measures for the solution of a conflict, which are granted by the judges with a lot of frequency, when they should be these hardships more than educational constrainers but with support in programs of work that serves them like half of social, exceptional reinserción.